Romania - New E.U. Member State, A New Phase of Its Transition - Marius PROFIROIU; Alina PROFIROIU; Laura MINA; Marian NICA (Transylvanian Review of Administrative Sciences, 2011)
Ever since Romania started its transition in the 1990s, it consistently scored poorly in various comparative performance assessments aimed at rating developing countries. In this paper we analyze whether Romania has managed to overcome the transition period or not, by pointing out both the drawbacks as well as the progress that has been made over the transition period, but most of all since our accession to the European Union in 2007. We discuss the concept of good governance for a new EU member state, by focusing on the state of public governance in Romania, but also addressing the other two important actors in the society, the private sector and the civil society.